Intracountry Regional Inequalities in the Context of the Socioeconomic Status of Selected European Countries - Klamár, Radoslav; Ivanová, Monika; Kozoň, Ján (Geographica Pannonica, 2025)
The paper deals with the issue of intracountry inequalities in selected European countries with attention paid to the analysis of potential connections between the level of identified regional inequalities in the assessed countries and their socioeconomic status. Two frequently employed indicators were chosen to assess regional inequalities: Gross Domestic Product per capita in PPS and Income of Households per capita in PPS, employing the Gini coefficient and the coefficient of variation as the basic statistical measures. The obtained results refer to the highest level of regional inequalities in the countries of the former Socialist Bloc, while the strong influence of capitals was also confirmed in these countries on the level of inequalities. At the same time, the presumption that the decreasing socioeconomic status of the countries caused the increasing level of intracountry regional inequalities was largely confirmed.
Keywords: coefficient of variation; Gini coefficient; Gross Domestic Product; Income of Household; socioeconomic status; intracountry regional inequalities